Sustaining corporate philanthropy through fastabiqul khairat - Mhd. Sarif, Suhaimi (Academy of Contemporary Islamic Studies (ACIS) UiTM, 2017)
Abstract: Corporate philanthropy enables companies to gain and sustain competitive advantage and profitability. In the new competitive market, ethical, trustworthy, and valuable companies to the societal well-being are preferred by the market. The stakeholders theory argued that corporate philanthropy practice is placed at the peak of corporate social responsibility pyramid. In doing so, companies are competing to offer superior corporate philanthropy to the society. This phenomenal practice reaches the concept of competing in doing good deed, which is called as fastabiqul khairat. The study used qualitative personal interview with 10 chief executive officers of small medium enterprises (SMEs) who are practicing corporate philanthrophy to obtain their feedback on the impact of fastabiqul khairat in sustaining their corporate philanthropy. The informants argued that the matter of principles and choices made them choose to compete in their corporate philanthropy for the betterment of the society. They argued that corporate philanthropy as investment for doing good which can be returned as return of good investment in the forms of customer loyalty and social wellbeing.